1998
DOI: 10.1021/ic970844s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of a Series of Edge-Sharing Octahedral−Tetrahedral−Octahedral Linear Trinuclear Complexes [M3(L1O)4]2+, Where M = Mn2+, Co2+, Ni2+, Cu2+, and Zn2+and L1OH Is the “Heteroscorpionate” Ligand (2-Hydroxyphenyl)bis(pyrazolyl)methane

Abstract: The mixed functionality pyrazole/phenol ligand (2-hydroxyphenyl)bis(pyrazolyl)methane, L1OH, has been used to prepare a series of linear trimetallic systems with the general structural motif [M(3)(L1O)(4)](2+), where M = Mn(2+), Co(2+), Ni(2+), Cu(2+), and Zn(2+). Each of these complexes has been structurally characterized by X-ray crystallography giving the following structural parameters: [Zn(3)(L1O)(4)][BF(4)](2).H(2)O, C(52)H(44)N(16)B(2)F(8)O(5)Zn(3), monoclinic, a = 18.572(4) Å, b = 22.400(5) Å, c = 15.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(37 citation statements)
references
References 27 publications
5
32
0
Order By: Relevance
“…These values are in agreement with those reported in the literature for complexes where two Mn II ions are bridged by two phenolate ligands. [27,29,31,34] Comparable results are obtained for 1(ClO 4 ) 2 ·H 2 O: g ϭ 1.96 and J ϭ Ϫ2.9 cm Ϫ1 . Small deformations of the [Mn 2 O 2 ] diamond core unit could lead to the slight differences in the g and J values determined for compound 1, depending on the counterion.…”
Section: Magnetic Susceptibility Measurementsmentioning
confidence: 83%
“…These values are in agreement with those reported in the literature for complexes where two Mn II ions are bridged by two phenolate ligands. [27,29,31,34] Comparable results are obtained for 1(ClO 4 ) 2 ·H 2 O: g ϭ 1.96 and J ϭ Ϫ2.9 cm Ϫ1 . Small deformations of the [Mn 2 O 2 ] diamond core unit could lead to the slight differences in the g and J values determined for compound 1, depending on the counterion.…”
Section: Magnetic Susceptibility Measurementsmentioning
confidence: 83%
“…2) Steric shielding of the metal binding site provides extra kinetic stability for the complexes and decreases the propensity of the adjacent hydroxy group to adopt a bridging position between two metal ions. [39] 3) It is important to prevent the formation of Michael adducts between the substrate amine and the ligand in its p-benzoquinone state by steric protection, with regard to amine oxidase model systems in particular. [40] Triisopropylsilyl derivative 2 c (Scheme 1) was synthesised to gain access to a ligand that shuttles between the p-hydroquinone and the p-semiquinone radical state (one-electron transition) rather than between the p-hydroquinone and the p-benzoquinone forms (two-electron transition).…”
Section: Resultsmentioning
confidence: 99%
“…Stelzig et al [6] have reported the complexes [Mn II 2 L 3 (µ 3 -OMe)(MeOH)] 2 and Na[Mn II 3 (L 3 ) 2 (µ 2 -OAc)]·H 2 O·0.25THF, where L 3 ϭ 1,5-bis(3-Cl, 5-NO 2 -salicylideneamino)pentan-3-ol, a voluminous pentadentate ligand. The Mn 2ϩ coordination arrange- [7] To confirm the difference in the manganese environments in 2 and 3 we have recorded the MnK XANES (X-ray Absorption Near Edge Structure) spectra for these com- pounds ( Figure 4). The maximum B in the spectra of 2 and 3 ( Figure 4) corresponds to an electron transition from the Mn1s to the Mn4p level.…”
Section: Structures Of Compounds 1 Andmentioning
confidence: 99%